THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF THINK PAIR SHARE TOWARD ABILITY OF STUDENT COOPERATION IN LEARNING MATHEMATICS - Ayu Annisa; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The learning model used in Junior High School (SMP) Muhammadiyah 1 Yogyakarta has not been optimal to develop student cooperation. This research aims to determine (1) the presence or absence of difference in the ability of student cooperation in learning mathematics taught using cooperative learning model type of TPS with taught using direct learning model and (2) which learning model is more effective between cooperative learning model type of Think Pair Share (TPS) direct learning model toward the ability of student cooperation. This research is experimental. The population is the students of class VII SMP Muhammadiyah 1 Yogyakarta even semester academic year 2016/2017. By random sampling, samples selected class VIIF as the experimental class and class VIIG as the control class. Instrument data collection using the ability of student cooperation observation sheet. The observation sheet has been by construct validity. The prerequisite analysis test used a normality test using the Chi-square formula and a homogeneity test using the Bartlett test. Data analysis used is the hypothesis test using a t-test with a significant level of 5% and degrees of freedom 61. Based on the result of the hypothesis, I test obtained . Because , so is rejected. There are differences in student cooperation in learning mathematics, taught using a cooperative learning model type of TPS with a direct learning model. Furthermore, the results of the hypothesis II test is obtained . Because , so is rejected. Thus, TPS's cooperative learning model type is more effective than the direct learning model toward student cooperation.